2016
DOI: 10.13080/z-a.2016.103.052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cucumber grafting on yield and fruit sensory characteristics

Abstract: During the period 2014-2015 the effects of cucumber grafting on yield and fruit sensory characteristics were studied under glasshouse conditions. Three long type parthenocarpic cucumber cultivars were grafted on five cucurbit rootstocks. The aim of the study was to compare the yield, elements of productivity and fruit sensory characteristics in order to establish the most appropriate scion/rootstock combinations. The highest yield was recorded in combination cv. 'Kiara F 1 ' grafted on Cucurbita maxima × C. mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…'Cristal F1' grafted onto eggplant rootstocks was higher than tomato rootstocks [25]. In line with our results, Sabatino et al [19] reported that eggplant cv. 'Scarlatti' F1 grafted onto S. melongena × S. aethiopicum rootstock had higher total and marketable yield than plants grafted onto S. aethiopicum.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…'Cristal F1' grafted onto eggplant rootstocks was higher than tomato rootstocks [25]. In line with our results, Sabatino et al [19] reported that eggplant cv. 'Scarlatti' F1 grafted onto S. melongena × S. aethiopicum rootstock had higher total and marketable yield than plants grafted onto S. aethiopicum.…”
Section: Discussionsupporting
confidence: 91%
“…They explained that lower SSC can be one of the reasons of the lower sensory evaluation results. Similarly, in another experiment, Velkov and Pevicharova [19] confirmed that sensory evaluation of cucumber depended on scion-rootstock combinations and every scion showed a different reaction to the same rootstock.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…At present, grafting is widely used to alleviate the obstacles caused by continuous cropping of cucumber, but the production of grafted transplants takes time, resources, and it is labor intensive [16,17]. Additionally, the use of rootstock during the process of grafting has certain negative impacts on fruit shape, flavor, and quality of cucumber [18]. Thus, there is a need to find a simple and labor-saving method that protects cucumber plants from stress without altering the flavor and quality of the cucumber.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Other descriptive sensory studies do not use chemical standards but reference foods or no references at all. [5][6][7][8][9]12,13 food such as a cucumber for a reference can create a variance in the perception since even the same cucumber variety can vary in flavor between each fruit. Using a chemical reference allows for specific intensities of each descriptor to be created uniformly for each training session, therefore minimizing the variance as to what intensity and flavor each panelist perceives.…”
Section: ■ Introductionmentioning
confidence: 99%